The Role of Financial Literacy and Spiritual Intelligence in The Financial Management of Mompreneurs Culinary MSMEs in Galang District - Br Tarigan, Angel Vita Loka; Lubis, Kartika Sari (J-MAS (Jurnal Manajemen dan Sains), 2024)
The purpose of this study was to examine the role of financial literacy and spiritual intelligence on the financial management of mothers' culinary MSME players in Galang District. This research is a quantitative study with a population of 57 MSME players in the culinary sector in Galang District. Data was collected using a questionnaire given to 57 respondents. The analysis technique of this research is the research method is a descriptive approach using the SEM PLS analysis technique using SMARTPLS 4 software. The results of the study (1) financial literacy as a positive and significant effect on financial management, (2) spiritual intelligence has a positive but insignificant effect on financial management. The soaring prices of basic necessities urge women with the status of housewives to trade small to sustain the family economy. For this reason, in running their business, mothers must also understand the importance of financial literacy and spiritual intelligence in managing their business finances.